Design and Development of a Product Data Traceability System Capable of Printing Web-Based Information Labels - Jamal Haiqal Bahanan; Prasaja Wikanta; Fitriyanti Nakul (International Journal of Computer Technology and Science, 2025)
The Printed Circuit Board (PCB) industry increasingly relies on automation and digitalization to improve efficiency and accuracy in production and distribution processes. One common practice is the use of labels containing product information in the form of barcodes or QR codes, which allow automatic data input and reduce the risk of human error compared to manual writing. However, in current practices, these labels are only attached to PCBs after they have been placed inside casings. This creates a significant limitation, as access to the label information requires disassembling the casing whenever product verification, tracking, or troubleshooting is needed. Such a process not only consumes additional time and resources but also increases the risk of damaging the product. To overcome this challenge, this study proposes the development of a traceability system designed to accurately monitor the location, identity, and status of PCBs throughout the distribution process. The system was implemented as a web-based application capable of generating and printing product information labels in the form of barcodes and QR codes. Each label functions as a unique identifier, ensuring that every PCB can be distinctly tracked from production to final product assembly. All data associated with the labels is automatically stored in a centralized database, providing real-time accessibility, simplifying information management, and enabling faster decision-making in the event of quality control issues. System evaluation was carried out through rigorous testing, which showed a 100% success rate in generating, storing, and retrieving product information without errors. The findings indicate that the proposed traceability system is both effective and efficient, and it offers a practical solution for industries seeking to enhance supply chain visibility, improve product accountability, and reduce operational inefficiencies in PCB distribution and lifecycle management.